FACTORS ANALYSIS OF EMPLOYEE ENGAGEMENT AT PT. PLN WILAYAH SULUTTENGGO - Kristanti, Nathania .; Pangemanan, Sifrid .; Rumokoy, Farlane S (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: This research is quantitative type of research which uses primary data obtained through questionnaire and uses Confirmatory Factor Analysis (CFA) as the analytical tool. The population of this research is the employee at PT. PLN Wilayah Suluttenggo where the sample size is taken from 100 employees. In this research, there are 20 variables that defined as factors that influence employee engagement at PT. PLN Wilayah Suluttenggo. The analysis and discussion from this research there are 13 variables that correlated with the factor that already conducted. The findings from the factoring process there are 4 factors that influence employee engagement at PT. PLN Wilayah Suluttenggo. First factor is Organizational Commitment with 6 independent variables (Employee Training, Work Environment, Socialization, Internal CSR, Co-Workers Support, and Development). Second factor is Organizational Justice with 3 independent variables (Reward, Internal Communication, and Job Characteristics). Third Factor is Organizational Performance with 3 independent variables (Empowerment, Recruitment, and Selection). Fourth factor is leadership style with one independent variable. This result show that company needs to maintain and improve those 4 important factor to reach employee engagement which are Organizational Commitment, Organizational Justice, Organizational Performance, and Leadership Style.Keywords: employee engagement, confirmatory factor analysis.